2013
DOI: 10.4103/0976-3147.118778
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cervical spinal tumor with large inferio.lateral extension through anterolateral (interscalene and transforaminal) approach

Abstract: Cervical spinal tumor with large lateral extension is usually removed through posterolateral approach and rarely through anterolateral approach. A young man presented with neck pain and brachialgia. Cervical spinal MRI showed a intraspinal tumor with huge extraforaminal paraspinal extension. We removed the tumor through anterolateral (interscalene and transforaminal) approach. Post operatively patient recovered from his sufferings and returned to normal life. Here we report the case along with operative techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In the current study, paresthesia was found the second most common symptom. Previous data showed that 70% of spinal schwannoma arose from sensory root, 20% from motor root, and rested from a mixture of both ( 16 ). Thus, abnormal motor function was relatively uncommon in the complaints of SS patients and usually occurred when tumors cause severe spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, paresthesia was found the second most common symptom. Previous data showed that 70% of spinal schwannoma arose from sensory root, 20% from motor root, and rested from a mixture of both ( 16 ). Thus, abnormal motor function was relatively uncommon in the complaints of SS patients and usually occurred when tumors cause severe spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Journal of Neuroscience in Rural Practice, Chowdhury et al .,[ 1 ] present a rare case of C7 spinal dumbbell schwannoma with large inferolateral extension removing through anterolateral (interscalenic and transforaminal) approach. I would like to take this opportunity to discuss the recent advances in the management of dumbbell spinal schwannomas.…”
mentioning
confidence: 99%